2020
DOI: 10.5009/gnl18419
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Clinical Predictive Factors Affecting the Outcome of Second-Line Chemotherapy for Gemcitabine-Refractory Advanced Pancreatic Cancer

Abstract: Background/Aims: The benefit of second-line chemotherapy (SL) after failed first-line chemotherapy (FL) in patients with advanced pancreatic cancer has not yet been established. We evaluated the clinical characteristics affecting the benefits of SL compared to best supportive care (BSC), identified the prognostic factors, and ultimately devised a model of clinical parameters to assist in making decision between SL and BSC after the failure of gemcitabine-based FL. Methods: The records of patients who received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Several studies have reported factors that can predict the survival outcomes of patients who undergo second-line chemotherapy [9,10,[14][15][16][17][18]. Among several clinical and biochemical variables, PS is one of the most common and important prognostic factors in patients receiving second-line chemotherapy [9,[14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported factors that can predict the survival outcomes of patients who undergo second-line chemotherapy [9,10,[14][15][16][17][18]. Among several clinical and biochemical variables, PS is one of the most common and important prognostic factors in patients receiving second-line chemotherapy [9,[14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, several studies reported second-line chemotherapy to be less efficient in patients with higher metastatic extent, particularly peritoneal metastases. 25,26 In addition, general condition compatible with full chemotherapy doses and slower disease evolution (diagnosis > 18 months before treatment initiation) was associated with prolonged tumor control under LV5FU2-carboplatin. Similarly, in a previous series, second-line chemotherapy achieved longer OS in patients who had longer first-line treatment duration.…”
Section: Discussionmentioning
confidence: 99%
“…43 In this series patients had received gemcitabine-based adjuvant or first line treatment (which were considered together) and went on to receive fluoropyrimidine-based (FOLFORINOX, FOLFOX, Cape/OX, or folinic acid/etoposide/cisplatin-FEP) second line. In another series from Taiwan, 43 decision-making and providing valuable information for discussions with pretreated metastatic pancreatic cancer patients and their families.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a careful evaluation and fair discussion of potential risks and benefits of second‐line treatment with patients and their families is mandatory and, perhaps, more important than the specific regimen selected. Individual prognostic factors have been proposed in this setting (PS, tumor burden, treatment response and duration of first‐line therapy, second‐line therapy regimen, and circulating biomarkers) and attempts have been made to integrate them into prognostic nomograms 43,44 . In a large retrospective Korean series, a nomogram for predicting OS on second‐line chemotherapy for mPC was devised based on number of metastatic lesions, presence of peritoneal metastases, occurrence of thrombotic events during first line, and CA19.9 levels; Harrel's C values for the development and validation cohorts were 0.62 and 0.56, respectively 43 .…”
Section: Discussionmentioning
confidence: 99%